Notes on ghosts, disputes and killer bodies - Boelen, Jan; Kennedy, Gabrielle (Design Academy, 2017)
At the Salon del Mobile 2017, Design Academy Eindhoven shows #TVclerici, a live TV studio where media is presented in the making. It is an experiment with facts and fiction, props and performance, as well as individual bodies and objects. An alternative reality is created for a world of designed fakery, from biometrics, cybernetics, and GPS fences, to gendered architecture and the era of khaki. This small book takes a behind-the-scenes look to reveal the underlying conversations, inspirations, controversies, narratives, and points of view. In addition, it uncovers how the positions taken by the students connect to what is going on in the world, beyond the safe confines of the academy
"This present publication accompanies Design Academy Eindhoven's Salone del Mobile 2017 exhibition, DAE #TVclerici. It is not a catalogue however" (Vorwort)
Keywords: Design Academy Eindhoven